Highest Obesity Category Associated With Largest Decrease in N‐Terminal Pro‐B‐Type Natriuretic Peptide in Patients Hospitalized With Heart Failure With Preserved Ejection Fraction. Issue 15 (4th August 2020) - Vaishnav, Joban; Chasler, Jessica E.; Lee, Yizhen J.; Ndumele, Chiadi E.; Hu, Jiun‐Ruey; Schulman, Steven P.; Russell, Stuart D.; Sharma, Kavita
Abstract : Background: Heart failure with preserved ejection fraction (HFpEF) constitutes half of hospitalized heart failure cases and is commonly associated with obesity. The role of natriuretic peptide levels in hospitalized obese patients with HFpEF, however, is not well defined. We sought to evaluate change in NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) levels by obesity category and related clinical outcomes in patients with HFpEF hospitalized for acute heart failure. Methods and Results: A total of 89 patients with HFpEF hospitalized with acute decompensated heart failure were stratified into 3 obesity categories: nonobese (body mass index [BMI] <30.0 kg/m 2, 19%), obese (BMI 30.0–39.9 kg/m 2, 29%), and severely obese (BMI ≥40.0 kg/m 2, 52%), and compared for percent change in NT‐proBNP during hospitalization and clinical outcomes. Clinical characteristics were compared between patients with normal NT‐proBNP (≤125 pg/mL) and elevated NT‐proBNP. Admission NT‐proBNP was inversely related to BMI category (nonobese, 2607 pg/mL [interquartile range, IQR: 2112–5703]; obese, 1725 pg/mL [IQR: 889–3900]; and severely obese, 770.5 pg/mL [IQR: 128–1268]; P <0.01). Severely obese patients had the largest percent change in NT‐proBNP with diuresis (−64.8% [95% CI, −85.4 to −38.9] versus obese −40.4% [95% CI, −74.3 to −12.0] versus nonobese −46.9% [95% CI, −57.8 to −37.4]; P =0.03). Nonobese and obese patients had significantly worse 1‐year survival compared with severely obese patients (63% versus 76% versus 95%, respectively; P <0.01). Patients with normal NT‐proBNP (13%) were younger, with higher BMI, less atrial fibrillation, and less structural heart disease than those with elevated NT‐proBNP. Conclusions: In hospitalized patients with HFpEF, NT‐proBNP was inversely related to BMI with the largest decrease in NT‐proBNP seen in the highest obesity category. These findings have implications for the role of NT‐proBNP in the diagnosis and assessment of treatment response in obese patients with HFpEF.